2018
DOI: 10.1128/aem.01049-17
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Amendments Alter Microbial Community Structure and Net Mercury Methylation Potential in Sediments

Abstract: Neurotoxic methylmercury (MeHg) is produced by anaerobic Bacteria and Archaea possessing the genes hgcAB, but it is unknown how organic substrate and electron acceptor availability impacts the distribution and abundance of these organisms. We evaluated the impact of organic substrate amendments on mercury (Hg) methylation rates, microbial community structure, and the distribution of hgcAB+ microbes with sediments. Sediment slurries were amended with short-chain fatty acids, alcohols, or a polysaccharide. Minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 66 publications
6
37
1
Order By: Relevance
“…Nutrient cycling and cometabolic Hg transformations stand to be closely linked in Hg methylation hotspots such as periphytic microbial mats (Olsen, Brandt, & Brooks, ), aquatic sediments (Correia & Guimarães, ; Fleming, Mack, Green, & Nelson, ) and waterlogged soils (Eklof et al, ). While our study makes a case for sulphur cycling as a coupling point for competing cometabolic Hg transformations, other nutrients such as iron (Bravo et al, ; Fleming et al, ; Sugio et al, ; Wiatrowski et al, ) and organic carbon (Christensen et al, ; Grégoire et al, ; Grégoire & Poulain, ) that are known to control Hg methylation and reduction have the potential to fulfil a similar role. Curiously, the coupling between other macronutrients under strong microbial control, such as nitrogen, and Hg cycling remains unexplored despite the importance of nitrogen cycling in aquatic and terrestrial ecosystems.…”
Section: Resultsmentioning
confidence: 91%
“…Nutrient cycling and cometabolic Hg transformations stand to be closely linked in Hg methylation hotspots such as periphytic microbial mats (Olsen, Brandt, & Brooks, ), aquatic sediments (Correia & Guimarães, ; Fleming, Mack, Green, & Nelson, ) and waterlogged soils (Eklof et al, ). While our study makes a case for sulphur cycling as a coupling point for competing cometabolic Hg transformations, other nutrients such as iron (Bravo et al, ; Fleming et al, ; Sugio et al, ; Wiatrowski et al, ) and organic carbon (Christensen et al, ; Grégoire et al, ; Grégoire & Poulain, ) that are known to control Hg methylation and reduction have the potential to fulfil a similar role. Curiously, the coupling between other macronutrients under strong microbial control, such as nitrogen, and Hg cycling remains unexplored despite the importance of nitrogen cycling in aquatic and terrestrial ecosystems.…”
Section: Resultsmentioning
confidence: 91%
“…Based on a higher number of sequenced microbial genomes now available, Christensen et al () developed a broad range hgcAB primer pair that improved the coverage of prior developed primers by 10% (Bae et al ; Schaefer et al ), and several clade‐specific PCR primers to improve amplification of the various members of the Hg II ‐methylating community (Christensen et al ) (Table ). In sediments, these clade‐specific primers were useful to detect Hg II ‐methylating δ‐Proteobacteria and Archaea but failed to detect Hg II ‐methylating Firmicutes (Christensen et al ).…”
Section: Toward a Better Understanding Of Microbial Methylmercury Formentioning
confidence: 99%
“…Despite the differences in primer pairs used in the studies mentioned earlier (Table ), until now, data globally suggested that in hgcA + δ‐Proteobacteria communities are abundant in surface sediments, but in some sites hgcA + methanogens and other hgcA + uncultivated groups are prevalent (Christensen et al , ; Vishnivetskaya et al ; Bravo et al ; Jones et al ). Among δ‐Proteobacteria , syntrophs and Geobacter spp.…”
Section: Toward a Better Understanding Of Microbial Methylmercury Formentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, clade-specific quantitative PCR (qPCR) assays were developed to quantify the abundance of hgcA gene of the main methylators [10]. Hence, hgcAB and hgcA distribution can be used to predict occurrence of potential Hg methylators in the environment [11]. Understanding hgcAB and hgcA distribution is essential for estimating MeHg production in the water column and biomagnification in food webs [12].…”
Section: Introductionmentioning
confidence: 99%